Solidarity liability of the cooperatives part of the Unimed Group – a Brazilian private healthcare insurance - Scheffer, Mario; Robba, Rafael (Journal of Health Law, 2016)
Unimed medical cooperatives – a Brazilian private health insurance- are a very expressive group in the Brazilian supplementary healthcare market, as they bring together the largest number of beneficiaries and present the highest turnover in the sector. In light of the decision of the Brazilian Superior Court of Justice (STJ) recognizing the solidarity liability related to obligations of any company belonging to the group Unimed, this article analyzes arguments and implications of this judgment. The transparency obligation stems from the basic consumer’s right to receive clear and adequate information on the marketed services and products. As for the good faith, it is linked to the loyalty that the parties must maintain at every stage of the contract, in respect to the expectations created. This article concludes that the STJ’s position, related to the responsibility of all companies of the Unimed Group, is a logical and necessary outcome.